2015
DOI: 10.1111/bju.13377
|View full text |Cite
|
Sign up to set email alerts
|

Multiphoton microscopy for rapid histopathological evaluation of kidney tumours

Abstract: ObjectiveTo explore the potential of multiphoton microscopy (MPM) for rapid evaluation and triaging of ex vivo kidney tissue. Materials and MethodsFresh neoplastic and non-neoplastic tissues from nephrectomy specimens (n = 40) were imaged with MPM and later submitted for routine histopathology. ResultsOn MPM, normal kidney architecture was evident and clearly distinguishable from tumour. Forty malignant tumours (20 clear-cell renal cell carcinomas [RCCs], 10 papillary RCCs, five chromophobe RCCs and five papil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 31 publications
0
14
0
Order By: Relevance
“…The various components of the atherosclerotic plaques were defined based on their morphological features (similar to that seen on H&E) as well as their well-known autofluorescence or SHG signals on MPM (Denk et al, 1990;Zipfel et al, 2003;Tewari et al, 2011;Jain et al, 2014;Jain et al, 2015;Jain et al, 2016). All the H&E images shown in the figures correspond to the samples imaged with MPM.…”
Section: Resultsmentioning
confidence: 99%
“…The various components of the atherosclerotic plaques were defined based on their morphological features (similar to that seen on H&E) as well as their well-known autofluorescence or SHG signals on MPM (Denk et al, 1990;Zipfel et al, 2003;Tewari et al, 2011;Jain et al, 2014;Jain et al, 2015;Jain et al, 2016). All the H&E images shown in the figures correspond to the samples imaged with MPM.…”
Section: Resultsmentioning
confidence: 99%
“…In their study, it distinguished RCC histological subtypes based on their tissue architecture, with a diagnostic accuracy of 95%. 20 It was suggested that MPM may potentially be used for real time unstained kidney tissue biopsy diagnosis and surgical margin assessment in future. 20 The findings in our report support the other reports that the presence and integrity of RCC pseudocapsules are known to vary between tumours.…”
Section: Discussionmentioning
confidence: 99%
“…Multiphoton microscopy has been used in research to differentiate neoplastic from nonneoplastic tissue and to characterize various tumors. [15][16][17][18] Further, Jain et al 19 have characterized various malignant kidney tumors on MPM and have achieved a high diagnostic accuracy of 98% in subtyping these tumors. Although this study included few cases of chRCC, it lacked oncocytoma cases.…”
Section: Discussionmentioning
confidence: 99%
“…13,14 It has been used to image fresh and fixed human tissues for differentiating neoplastic from nonneoplastic lesions and to characterize various tumor types, including kidney tumors. [15][16][17][18][19] The purpose of the current study was to explore MPM as a potential alternative and rapid diagnostic tool for differen-tiating oncocytoma from chRCC. Because this was a proofof-concept study, typical cases (readily diagnosed with H&E) of oncocytoma and chRCC were included, with the aim of characterizing unique MPM signatures of each tumor type that could aid in their differential diagnosis.…”
mentioning
confidence: 99%